PENGARUH KONSERVATISME AKUNTANSI, STRUKTUR MODAL, DAN PERTUMBUHAN LABA TERHADAP KUALITAS LABA (Studi Empiris pada Perusahaan Sektor Pertambangan Industri Batu Bara yang terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Amaliya Wijaya; Syamsul Mu’arif (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This study entitled The Effect of Accounting Conservatism, Capital Structure, and Profit Growth on Earnings Quality. The purpose of this research is to determine the effect of Accounting Conservatism, Capital Structure, and Profit Growth on Profit Quality in Coal Industry Mining companies listed on the Indonesia Stock Exchange from the 2017 period to the 2022 period. The data used for this research are the financial statements of each -each sample company, published on the websites www.idx.co.id and www.sahamu.com. The analytical method used in this research is a quantitative method, with classical assumptions, as well as statistical analysis, namely linear regression analysis of panel data with a significance level of 5%. The variables of this study are Accounting Conservatism as a variable X1, Capital Structure as a variable X2, Profit Growth as a variable X3, and Earnings Quality as a variable Y. Statistical testing uses e-Views 12. The results of this study indicate that accounting conservatism, capital structure, and growth earnings influence simultaneously on the quality of earnings. Accounting conservatism, and profit growth have a partial effect on earnings quality. And Capital Structure has no effect on Earnings Quality.